(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract: This study aims to find out the level of stress in the family life of the employers at the University of Kasdi Merbah Ouargla, as well as studying the differences between the sample members in the level of pressures of family life according to the difference gender, family status of the worker and the nature of housing. In line with the nature of the subject studied, and in order to achieve the objectives of the study, we used the descriptive approach, where the study sample consisted of (198) professional workers who were stratified random sampling selected, where they were subjected to a questionnaire about Amani Abdul Maksoud and Tahani Othman’s family life pressures. What is meant after modifying it and studying its psychometric properties, and after processing the data using the copy 25 of the spss statistical program. The results of the analysis led to the following: - The level of family life stress among vocational workers at the University of Kasdi Merbah Ouargla is low. - There are no statistically significant differences in the level of stress in family life among vocational workers at the university of Kasdi Merbah Ouargla, according to gender and the nature of housing. While there are statistically significant differences in the level of family life stress among vocational workers at the university of Kasdi Merbah Ouargla, according to family status. Keywords: family life stress, vocational workers. ملخص: تهدف هذه الدراسة إلى معرفة مستوى ضغوط الحياة الأسرية للعمال المهنيين بجامعة قاصدي مرباح ورقلة، وكذا دراسة الفروق بين أفراد العينة في مستوى ضغوط الحياة الأسرية باختلاف الجنس والحالة العائلية للعامل وطبيعة السكن، وتماشيا مع طبيعة الموضوع المدروس ومن أجل تحقيق أهداف الدراسة استخدمنا المنهج الوصفي حيث تكونت عينة الدراسة من (198) عاملا مهنيا اختيرو بطريقة العينة العشوائية الطبقية حيث طبق عليهم إستبيان ضغوط الحياة الأسرية لأماني عبد المقصود وتهاني عثمان بعد تعديله ودراسة خصائصه السيكومترية، وبعد معالجة البيانات باستخدام النسخة 25 للبرنامج الإحصائي spss أفضت نتائج التحليل إلـــــــــى: -أن مستوى ضغوط الحياة الأسرية لدى العمال المهنيين بجامعة قاصدي مرباح ورقلة منخفض. -عدم وجود فروق ذات دلالة إحصائية في مستوى ضغوط الحياة الأسرية لدى العمال المهنيين بجامعة قاصدي مرباح ورقلة باختلاف الجنس وباختلاف طبيعة السكن. بينما توجد فروق ذات دلالة إحصائية في مستوى ضغوط الحياة الأسرية لدى العمال المهنيين بجامعة قاصدي مرباح ورقلة باختلاف الحالة العائلية. كلمات دالة: ضغوط الحياة الأسرية، العمال المهنيين.